2021
DOI: 10.1177/01926365211045459
|View full text |Cite
|
Sign up to set email alerts
|

School Administrators’ Intentions to Promote Adapted Physical Education

Abstract: A survey, developed with the Theory of Planned Behavior, was used to assess school administrators’ intention to promote adapted physical education (APE). Survey results indicated that when school administrators’ attitudes and subjective norms were favorable, the intention to promote APE was subsequently higher. The results indicate that if we expect public school administrators to promote APE in schools, they must know the importance of high-quality physical education to students with disabilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…Along with having knowledge of APE, when principals believe they can promote APE and have favorable beliefs and attitudes to promote high-quality APE, they are more likely to do so (Ajzen, 1991;Rizzo, 2020). Previous survey data has indicated the PBC construct was not significantly associated with school administrators' intentions to support APE; however, it was suggested this lack of significance may have been attributed to an overarching indifference toward APE (McNamara et al, 2021a). However, findings from the current study indicate that resources, a major component of PBC, influenced the perceived control administrators' feel they must promote and support APE.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Along with having knowledge of APE, when principals believe they can promote APE and have favorable beliefs and attitudes to promote high-quality APE, they are more likely to do so (Ajzen, 1991;Rizzo, 2020). Previous survey data has indicated the PBC construct was not significantly associated with school administrators' intentions to support APE; however, it was suggested this lack of significance may have been attributed to an overarching indifference toward APE (McNamara et al, 2021a). However, findings from the current study indicate that resources, a major component of PBC, influenced the perceived control administrators' feel they must promote and support APE.…”
Section: Discussionmentioning
confidence: 97%
“…TPB constructs, along with principals’ attributes, will measure and explain their intentions to promote APE. McNamara et al (2021a) recently assessed school administrators’ intention to support APE services using a survey grounded within the TPB. Linear regressions indicated that higher levels of attitudes and subjective norms related to supporting APE were related to being more likely to have intentions to support APE services.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 3 more Smart Citations